Lead-free piezoelectric magnetic composition, piezoelectric element, and device

By integrating a tungsten bronze-type compound sub-phase with an alkaline niobate perovskite-type oxide main phase in lead-free piezoelectric ceramic compositions, the challenges of maintaining piezoelectric properties under high voltage in high-load devices are effectively addressed, resulting in enhanced performance and stability.

JP2025039109APending Publication Date: 2025-03-21NITERRA CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023145961
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Lead-free piezoelectric ceramic compositions used in high-load devices, such as ultrasonic scalpel or ultrasonic scaler, face challenges in maintaining piezoelectric properties under high voltage conditions.

Method used

Incorporating a main phase of alkaline niobate perovskite-type oxide with a tetragonal peak ratio of 1.52 or more, and a sub-phase of tungsten bronze-type compound, which includes at least one of Nb, Ba, Ca, Sr, Na, and K, to enhance the piezoelectric properties and stability under high voltage.

Benefits of technology

The proposed composition significantly improves the piezoelectric properties and suppresses the deterioration of these properties under high voltage, ensuring reliable performance in high-load devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039109000001_ABST
    Figure 2025039109000001_ABST
Patent Text Reader

Abstract

To provide a lead-free piezoelectric magnetic composition, a piezoelectric element, and a device that can improve piezoelectric characteristics and suppress degradation of the piezoelectric characteristics under high voltage.SOLUTION: A lead-free piezoelectric magnetic composition includes a main phase made of an alkali niobate perovskite oxide and a subphase made of a tungsten bronze compound, and the tetragonal peak 002 / 020 ratio of the main phase is 1.52 or more. In this way, the tetragonal peak 002 / 020 ratio of the main phase made of an alkali niobate perovskite oxide is 1.52 or more, such that the piezoelectric properties of the lead-free piezoelectric ceramic composition can be improved. In addition, the subphase made of a tungsten bronze compound is mixed with the main phase, such that the deterioration of the piezoelectric properties of the lead-free piezoelectric ceramic composition under high voltage can be suppressed.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The technology disclosed by this specification relates to a lead-free piezoelectric composition, a piezoelectric element, and an apparatus using the same.

Background Art

[0002] Conventionally, as ceramics exhibiting piezoelectricity, PZT (lead zirconate titanate) has been widely used. However, since PZT contains lead in its components, its environmental impact has been regarded as a problem, and in recent years, the development of lead-free piezoelectric ceramic materials has been promoted. As one of the promising candidates for lead-free piezoelectric ceramic materials, there is a lead-free piezoelectric porcelain composition mainly composed of an alkali niobate-based perovskite-type oxide.

[0003] Patent Document 1 includes a main phase containing an alkali niobate / tantalate-based perovskite-type oxide of Nb (niobium) / Ta (tantalum), a sub-phase containing a spinel compound containing Ti (titanium), contains Mn (manganese), and the content ratio x of Ti is greater than 0 mol% and 4 mol% or less, and the content ratio x of Ti and the content ratio y of Mn satisfy the following relational expression x 2 / y ≦ 20.0. A lead-free piezoelectric porcelain composition is disclosed.

[0004] Patent Document 2 has a composition formula (A1 a M1 b ) c (Nb d1 , Mn d2 , M2 d3 )O 3+e (wherein element A1 is at least one of alkali metals, element M1 is at least one of Ba, Ca, Sr, element M2 is at least one of Ti, Zr, 0 < a < 1, 0 < b < 1, a + b = 1, c satisfies 0.80 < c < 1.10, 0 < d1 < 1, 0 < d2 < 1, 0 < d3 < 1, d1 + d2 + d3 = 1, and e represents a value of oxygen deficiency or excess). A lead-free piezoelectric porcelain composition including a main phase composed of an alkali niobate-based perovskite-type oxide and satisfying b / (d2 + d3) > 1.0 is disclosed.

Prior Art Documents

[0005] [Patent Document 1] International Publication No. 2022 / 215666 [Patent Document 2] International Publication No. 2023 / 026614 Summary of the Invention [Problem to be solved by the invention]

[0006] When the above-mentioned lead-free piezoelectric ceramic composition is applied to a piezoelectric element of a device that operates under high load, such as an ultrasonic scalpel or an ultrasonic scaler, it is important that the piezoelectric characteristics do not deteriorate under high voltage, and there is a demand for further improvement in the characteristics of the lead-free piezoelectric ceramic composition. [Means for solving the problem]

[0007] (1) In order to achieve the above object, the lead-free piezoelectric ceramic composition of the present invention has the following features: That is, the lead-free piezoelectric ceramic composition of the application example of the present invention includes a main phase made of an alkali niobate-based perovskite-type oxide and a subphase made of a tungsten bronze-type compound, and the tetragonal peak 002 / 020 ratio of the main phase is 1.52 or more.

[0008] (2) In the lead-free piezoelectric ceramic composition according to the application example of (1) above, the tungsten bronze type compound exhibits a peak at 13.2°±0.1°.

[0009] (3) In the lead-free piezoelectric ceramic composition according to the application example of (1) or (2) above, the tungsten bronze type compound contains Nb and at least one of Ba, Ca, Sr, Na, and K.

[0010] (4) In the lead-free piezoelectric ceramic composition according to any one of the application examples of (1) to (3) above, the alkali niobate-based perovskite oxide contains Mn.

[0011] (5) Also, in the lead-free piezoelectric ceramic composition of any of the application examples (1) to (4) above, the alkali niobate perovskite-type oxide has a composition formula (A1 a M1 b ) c (Nb d1 , Mn d2 , M2 d3 )O 3+e (wherein element A1 is at least one of alkali metals, element M1 is at least one of Ba, Ca, Sr, element M2 is at least one of Ti, Zr, 0 < a < 1, 0 < b < 1, a + b = 1, c satisfies 0.80 < c < 1.10, 0 < d1 < 1, 0 < d2 < 1, 0 < d3 < 1, d1 + d2 + d3 = 1, and e represents a value of oxygen deficiency or excess), and satisfies b / (d2 + d3) > 1.0.

[0012] (6) Also, the piezoelectric element of the application example of the present invention includes a piezoelectric body made of any of the lead-free piezoelectric ceramic compositions (1) to (5) above, and an electrode in contact with the piezoelectric body.

[0013] (7) Also, the device of the application example of the present invention includes the piezoelectric element of (6) above.

[0014] (8) Also, the device of the application example of (7) above is selected from the group consisting of a ultrasonic scalpel, a ultrasonic scaler, a ultrasonic cleaner, a ultrasonic processing machine, a piezoelectric transducer, a ultrasonic motor, a piezoelectric gyro sensor, a piezoelectric filter, and a knock sensor.

Advantages of the Invention

[0015] According to the lead-free piezoelectric magnetic composition, piezoelectric element, and device disclosed herein, the piezoelectric properties can be enhanced, and the deterioration of the piezoelectric properties under high voltage can be suppressed.

Brief Description of the Drawings

[0016] [Figure 1] (a) and (b) are perspective views of the piezoelectric element of the embodiment, respectively. [Diagram 2] FIG. 1 is a schematic diagram showing an ultrasonic scalpel according to an embodiment. [Diagram 3] FIG. 1 is a schematic diagram showing an ultrasonic scaler according to an embodiment. [Figure 4] 1 is a schematic diagram showing an ultrasonic cleaner according to an embodiment; [Diagram 5] 1 is a schematic diagram showing an ultrasonic processing machine according to an embodiment; [Figure 6] 1 is a schematic diagram showing a piezoelectric transducer according to an embodiment; [Figure 7] 1 is a schematic diagram showing an ultrasonic motor according to an embodiment; [Figure 8] 1 is a schematic diagram showing a piezoelectric gyro sensor according to an embodiment; [Figure 9] 1 is a schematic diagram illustrating a piezoelectric filter according to an embodiment of the present invention. [Figure 10] FIG. 2 is a schematic diagram illustrating a knock sensor according to an embodiment. [Figure 11] 1 is a table showing various test results of examples and comparative examples. [Figure 12] 1 is a graph showing diffraction peaks in a part of the angle range of powder X-ray diffraction in Examples 1 to 3 and Comparative Example 2. [Figure 13] 1 is a graph showing vibration characteristics of vibrators made of Examples 1 to 3, Comparative Example 2, and a general PZT. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Next, an embodiment of the present invention will be described with reference to the drawings. In order to facilitate understanding of the description, the same reference numerals are used for the same components in each drawing, and duplicated descriptions will be omitted. In the configuration diagrams, the size of each component is conceptually shown, and does not necessarily represent the actual dimensional ratio.

[0018] [Embodiment] (Structure of lead-free piezoelectric ceramic composition) The lead-free piezoelectric ceramic composition of the present invention comprises a main phase made of an alkali niobate perovskite-type oxide having piezoelectric properties, and a subphase made of a tungsten bronze-type compound, and the tetragonal peak 002 / 020 ratio of the main phase is 1.52 or more.

[0019] In this way, when the tetragonal peak 002 / 020 ratio of the main phase made of an alkali niobate perovskite oxide is 1.52 or more, the piezoelectric properties of the lead-free piezoelectric ceramic composition can be improved.

[0020] A tungsten bronze compound is a compound having a tungsten bronze structure represented by the following composition formula (1).

[0021] A k B l O 15+δ …(1)

[0022] In the above composition formula (1), A contains one or more monovalent or divalent elements, and B contains one or more divalent or pentavalent elements. In addition, k, l, and δ in the composition formula (1) are typically k=3, l=5, and δ=0, respectively, but may deviate from the standard values ​​as long as the tungsten bronze structure can be maintained (the characteristics do not change significantly), and may contain impurity elements. The preferred ranges of k, l, and δ in the composition formula (1) are, for example, 2.8≦k≦3.2, 4.8≦l≦5.2, and -1≦δ≦0.

[0023] A specific example of the composition represented by formula (1) is Ba3Nb5O 15 ,Ba2KNb5O 15 ,Ba2NaNb5O 15 The composition of the tungsten bronze type compound that becomes the subphase may deviate from the compositional ratio of the above composition formula (1) or may contain some other elements. Also, in addition to the subphase consisting of the tungsten bronze type compound, there may be a spinel type compound mixed in as a subphase.

[0024] The subphase made of a tungsten bronze type compound, when mixed with the main phase, facilitates polarization of the lead-free piezoelectric ceramic composition. It also suppresses the deterioration of the piezoelectric properties, particularly the vibration properties, of the lead-free piezoelectric ceramic composition under high voltage. This is presumably because the inclusion of the subphase made of a tungsten bronze type compound increases the hardness of the entire lead-free piezoelectric ceramic composition.

[0025] In the lead-free piezoelectric ceramic composition, the content of the subphase made of a tungsten bronze type compound is such that the ratio of the main peak of the subphase made of a tungsten bronze type compound near 13.2° (13.2°±0.1°) is 0 to 4.2 when the intensity of the main peak of the main phase made of an alkali niobate perovskite type oxide is taken as 100. The content of the subphase is preferably 0.89 to 1.67, and more preferably 1.5 to 1.67.

[0026] The presence of a subphase consisting of a tungsten bronze type compound in the lead-free piezoelectric ceramic composition can be confirmed by the presence of a peak different from that of the main phase at at least one of 13.2°±0.1°, 11.5°±0.1°, and 12.4°±0.1° in a powder X-ray diffraction method.

[0027] The tungsten bronze type compound preferably exhibits a peak at 13.2°±0.1° in powder X-ray diffraction, which makes it easy to confirm that the piezoelectric ceramic composition contains a subphase made of a tungsten bronze type compound.

[0028] The tungsten bronze type compound preferably contains Nb (niobium) and at least one of Ba (barium), Ca (calcium), Sr (strontium), Na (sodium), and K (potassium), which allows the tungsten bronze type compound to be specifically configured.

[0029] The alkali niobate perovskite-type oxide preferably contains Mn (manganese). Thereby, the mechanical quality factor Qm of the lead-free piezoelectric ceramic composition can be increased. In this case, Mn may be contained in the tungsten bronze-type compound.

[0030] The alkali niobate perovskite-type oxide is preferably a compound represented by the following compositional formula (2).

[0031] (A1 a M1 b ) c (Nb d1 ,Mn d2 ,M2 d3 )O 3+e …(2)

[0032] In the above compositional formula (2), the element A1 is at least one of alkali metals. It is preferable that the element A1 contains at least one of K (potassium), Na (sodium), and Li (lithium). The element M1 is at least one of alkaline earth metals Ca (calcium), Sr (strontium), and Ba (barium). The element M2 is at least one of Ti (titanium) and Zr (zirconium).

[0033] In the compositional formula (2), the element A1 and the element M1 are arranged at the A site (alkali site) of the perovskite structure, and Nb (niobium), Mn (manganese), and the element M2 are arranged at the B site.

[0034] As the values of the coefficients a to e in the compositional formula (2), among the combinations of values that form a perovskite structure, preferable values are selected from the viewpoint of the electrical properties or piezoelectric properties (particularly the piezoelectric constant d 33 ) of the lead-free piezoelectric ceramic composition.

[0035] Specifically, the coefficients a and b satisfy 0 < a < 1, 0 < b < 1, and a + b = 1, and a = 0 (that is, a composition containing no alkali metals) and b = 0 (that is, a composition containing no Ca, Sr, or Ba) are excluded.

[0036] The coefficient c for the entire A site satisfies 0.80 < c < 1.10, preferably 0.84 ≤ c ≤ 1.08, and more preferably 0.88 ≤ c ≤ 1.07.

[0037] The coefficients d1, d2, and d3 satisfy 0 < d1 < 1, 0 < d2 < 1, 0 < d3 < 1, and d1 + d2 + d3 = 1. Compositions with d1 = 0 (compositions不含 Nb), d2 = 0 (compositions不含 Mn), and d3 = 0 (compositions不含 both Ti and Zr) are excluded.

[0038] Among the coefficients 3 + e of oxygen, the coefficient e is a positive or negative value indicating oxygen deficiency or excess with respect to the coefficient of oxygen which is usually 3. The coefficient of oxygen (3 + e) can take a value such that the main phase constitutes a perovskite oxide. A typical value of the coefficient e is e = 0, and preferably 0 ≤ e ≤ 0.1. The value of the coefficient e can be calculated from the electrical neutrality condition of the composition of the main phase. However, as the composition of the main phase, a composition slightly deviating from the electrical neutrality condition is also acceptable.

[0039] The coefficients b, d2, and d3 satisfy b / (d2 + d3) > 1.0. If the coefficients b, d2, and d3 take values within this range, a lead-free piezoelectric ceramic composition with a high mechanical quality factor Qm can be obtained. The reason is presumed as follows.

[0040] It is believed that Mn dissolves in the Nb site as an acceptor, improving the mechanical quality factor Qm. However, Mn is difficult to dissolve in alkali niobate perovskite oxides, and is prone to segregation as a different phase in lead-free piezoelectric ceramic compositions. The ease of dissolution is believed to depend on the ionic radius and valence of the metal atom in the solid solution, and it is believed that trivalent Mn is difficult to dissolve in the B site, where pentavalent Nb is mainly located. On the other hand, divalent elements Ba, Ca, and Sr are easily dissolved in the A site, where monovalent alkali metals are located. It is presumed that the appropriate amount of Ba, Ca, and Sr, which have a valence close to that of Mn, dissolved in the A site helps Mn to dissolve in the B site. It is believed that by adjusting the composition ratio of Mn to Ba, Ca, and Sr so that b / (d2+d3)>1.0, an appropriate amount of Mn is dissolved in the B site, improving the mechanical quality factor Qm.

[0041] Although there is no particular upper limit to the value of b / (d2+d3), it is preferable that b / (d2+d3)≦2.0.

[0042] (Piezoelectric element) 1(a) and 1(b) are perspective views showing an example of a piezoelectric element according to an embodiment of the present invention. FIG. 1(a) shows a disk-shaped piezoelectric element 10, and FIG. 1(b) shows a doughnut-shaped piezoelectric element 10 with a through hole. The piezoelectric element 10 of the present invention includes a piezoelectric body 20 and electrodes 31 and 32 in contact with the piezoelectric body. The piezoelectric body 20 is made of the above-mentioned lead-free piezoelectric ceramic composition. One of the electrodes 31 and 32 is disposed on one side of the piezoelectric body 20, and the other is disposed on the other side of the piezoelectric body 20, so that the piezoelectric body 20 is sandwiched between the electrodes 31 and 32. Note that various shapes and configurations other than those described above can be adopted as the piezoelectric element.

[0043] (Device) The device according to the embodiment of the present invention includes the above-mentioned piezoelectric element 10. The device according to the embodiment of the present invention is preferably selected from the group consisting of an ultrasonic scalpel 40, an ultrasonic scaler 50, an ultrasonic cleaner 60, an ultrasonic processing machine 70, a piezoelectric transducer 80, an ultrasonic motor 90, a piezoelectric gyro sensor 100, a piezoelectric filter 110, and a knock sensor 120, for example.

[0044] (1) Ultrasonic scalpel 40 2 is a schematic diagram showing an ultrasonic scalpel 40 according to an embodiment of the present disclosure. The ultrasonic scalpel 40 includes an ultrasonic transducer 41 and an action member 43. The ultrasonic transducer 41 has the piezoelectric element 10 and is driven to generate ultrasonic vibrations when an electric signal is applied. The ultrasonic transducer 41 operates to transmit ultrasonic vibrations to the action member 43 configured in a shaft shape. The ultrasonic transducer 41 drives the action member 43 so as to cause an action of incising, ablating, or thermally coagulating hemostasis of biological tissue in the vicinity of the action member 43.

[0045] (2) Ultrasonic Scaler 50 3 is a schematic diagram showing an ultrasonic scaler 50 according to an embodiment of the present disclosure. The ultrasonic scaler 50 includes an ultrasonic transducer 41 and a dental tip 53. The ultrasonic transducer 41 has the piezoelectric element 10 and is driven to generate ultrasonic vibrations when an electric signal is applied. The ultrasonic transducer 51 operates to transmit ultrasonic vibrations to the dental tip 53.

[0046] (3) Ultrasonic Cleaner 60 4 is a schematic diagram showing an ultrasonic cleaner 60 according to an embodiment of the present disclosure. The ultrasonic cleaner 60 includes an ultrasonic transducer 41 and a cleaning container 63. The ultrasonic transducer 41 has the piezoelectric element 10 and is driven to generate ultrasonic vibrations when an electric signal is applied. An object 65 to be cleaned is placed in the cleaning container 63 containing a cleaning liquid, and ultrasonic vibrations generated by vibrating the ultrasonic transducer 41 are transmitted to the cleaning liquid, cleaning the object 65.

[0047] (4) Ultrasonic processing machine 70 5 is a schematic diagram showing an ultrasonic processing machine 70 according to an embodiment of the present disclosure. The ultrasonic processing machine 70 includes a base material 71, an ultrasonic transducer 41, a grindstone unit 75, and a spindle 77. The base material 71 is disk-shaped, and the grindstone unit 75 is formed on its outer periphery. The center of the base material 71 is fixed to the spindle 77.

[0048] The ultrasonic vibrator 41 has the piezoelectric element 10, and is driven to generate ultrasonic vibrations when an electric signal is applied. The driving direction of the ultrasonic vibrator 41 is a radial direction from the center of the base material 71 to the outer periphery. With the spindle 77 rotating about its axial direction while the ultrasonic vibrator 41 generates vibrations, the grindstone portion 75 formed on the outer periphery of the base material 71 can be pressed against the workpiece to cut the workpiece.

[0049] (5) Piezoelectric transducer 80 6 is a schematic diagram showing a piezoelectric transducer 80 according to an embodiment of the present disclosure. The piezoelectric transducer 80 includes a piezoelectric element 10.

[0050] (6) Ultrasonic motor 90 7 is a schematic diagram showing an ultrasonic motor 90 according to an embodiment of the present disclosure. The ultrasonic motor 90 includes an ultrasonic transducer 41, a rotor 93, and an output shaft 95. The ultrasonic transducer 41 includes the piezoelectric element 10. For example, when an AC voltage is applied to the piezoelectric element, a flexural traveling wave is generated in the ultrasonic transducer 41, and each point on the sliding surface of the ultrasonic transducer 41 moves elliptically. When the rotor 93 is pressed against the sliding surface of the ultrasonic transducer 41, the rotor 93 receives a frictional force from the ultrasonic transducer 41 and rotates in the opposite direction to the flexural traveling wave.

[0051] (7) Piezoelectric gyro sensor 100 8 is a schematic diagram showing a piezoelectric gyro sensor 100 according to an embodiment of the present disclosure. The piezoelectric gyro sensor 100 has a piezoelectric element 10 including a piezoelectric body 20 and electrodes 31 and 32 applied to both sides of the piezoelectric body 20.

[0052] (8) Piezoelectric filter 110 9 is a schematic diagram illustrating a laminated piezoelectric filter 110, which is one example of an embodiment of the piezoelectric filter. The laminated piezoelectric filter 110 has a columnar piezoelectric body 20 and a piezoelectric element 10 having electrodes 31 and 32 on both sides of the piezoelectric body 20.

[0053] (9) Knock sensor 120 10 is a schematic diagram of a knock sensor 120 which is an embodiment of the device of the present disclosure. The knock sensor 120 has a piezoelectric element 10 including a piezoelectric body 20 and electrodes 31 and 32.

[0054] [Manufacturing method of piezoelectric element] An example of a method for manufacturing the above-mentioned piezoelectric element 10 will be described below.

[0055] (Method of Preparing Calcined Powder of Main Phase) First, the necessary raw material powders of the main components of the alkali niobate perovskite oxide that will be the main phase are selected and weighed to obtain the desired composition. The raw material powders of the main components of the main phase may be oxides, carbonates, or hydroxides of the elements contained in the main phase. Ethanol is added to these raw material powders of the main phase, and the mixture is wet-mixed in a ball mill for preferably 15 hours or more to obtain a slurry. The resulting slurry is dried, and the resulting mixed powder is calcined, for example, in an air atmosphere at 600 to 1100°C for 1 to 10 hours to obtain a calcined powder of the main components of the main phase.

[0056] Next, the additives are selected as necessary and weighed out to be added in a predetermined amount to the calcined powder of the main component of the main phase. The raw powder of the additives may be oxides, carbonates, or hydroxides of the elements to be added as additives to the alkali niobate perovskite oxide that becomes the main phase. Then, ethanol is added to the powder obtained by mixing the calcined powder of the main component of the main phase with the additives, and the mixture is wet-mixed in a ball mill for preferably 15 hours or more to obtain a slurry. The mixed powder obtained by drying the slurry is calcined, for example, in an air atmosphere at 600°C to 1100°C for 1 hour to 10 hours to produce the calcined powder of the main phase.

[0057] In this way, calcined powder of the main phase can be produced. By producing calcined powder of the main components of the main phase and then adding additives, the piezoelectric properties of the main phase can be further improved. This is thought to be because segregation of the additives is less likely to occur. Note that the main components of the main phase refer to A1 and Nb in composition formula (2), for example, and the additive components of the main phase refer to M1, Mn, and M2. Calcined powder of the main phase may be produced by mixing raw material powder of the main components of the main phase and raw material powder of the additives at once, without producing calcined powder of the main components of the main phase.

[0058] (Method of Preparing Calcined Powder of Subphase) Separately from the above, a necessary one is selected from the raw material powders of the tungsten bronze type compound that will become the subphase, and weighed to obtain the desired composition. The raw material powders of the subphase may be oxides, carbonates, or hydroxides of the elements contained in the subphase. For example, Nb2O5 powder, BaCO3 powder, CaCO3 powder, SrCO3 powder, Na2CO3 powder, and K2CO3 powder are selected as necessary and weighed. Then, ethanol is added to these raw material powders of the subphase, and the mixture is wet-mixed in a ball mill for preferably 15 hours or more to obtain a slurry. The mixed powder obtained by drying the slurry is calcined, for example, in an air atmosphere at 600°C to 1300°C for 1 hour to 10 hours to produce a calcined powder of the subphase.

[0059] (Method of producing sintered body) Ethanol and a binder are added to the calcined powder of the main component and the calcined powder of the subphase prepared as described above, and the mixture is wet-mixed in a ball mill to obtain a slurry. The slurry is then dried to obtain granulated powder. The granulated powder is then filled into a mold and uniaxially pressed at a pressure of, for example, 20 MPa to form the powder into a desired shape. A CIP process (cold isostatic pressing process) is then performed at a pressure of, for example, 150 MPa to obtain a molded body. The obtained molded body (CIP pressed body) is sintered, for example, at 900°C to 1300°C in an air atmosphere for 1 to 10 hours, to obtain a piezoelectric body from the piezoelectric ceramic composition.

[0060] (Processing method) Next, the obtained piezoelectric body is cut and the top and bottom surfaces are processed according to the dimensional accuracy required for the piezoelectric element. In order to stabilize the characteristics of the piezoelectric body thus obtained, for example, an annealing process is performed under conditions of 800°C in air for 1 hour. After that, electrodes are formed on the surface of the obtained piezoelectric body by, for example, a sputtering method, and a polarization process is performed to obtain a piezoelectric element.

[0061] The above-mentioned manufacturing method is an example, and various other steps and processing conditions for manufacturing a piezoelectric element can be used. For example, instead of producing the calcined products of the main phase and the subphase separately in advance and then mixing and firing the powders of both, the raw materials may be mixed in a quantity ratio according to the final composition of the lead-free piezoelectric ceramic composition, and then fired. However, according to the method of producing the calcined products of the main phase and the subphase separately in advance and then mixing them, it is easier to control the compositions of the main phase and the subphase more strictly, so that it is possible to increase the yield of the lead-free piezoelectric ceramic composition.

[0062] [Examples and Comparative Examples] Example 1 The main phase has a composition of K 0.5 Na 0.5 K2CO3 powder, Na2CO3 powder, and Nb2O5 powder were weighed as raw material powders for the main components of the main phase to produce NbO3. Ethanol was added to these raw material powders for the main components of the main phase, and the mixture was wet mixed in a ball mill for 15 hours or more to obtain a slurry. The mixed powder obtained by drying the slurry was then calcined at 930°C for 4 hours in an air atmosphere to produce a calcined powder of the main components of the main phase.

[0063] Next, the additives were weighed out so that the calcined powder of the main component of the main phase was 100 mol%, and the additives were added in an amount of 2.0 mol% BaCO3, 2.0 mol% CaCO3, 1.0 mol% TiO2, and 2.0 mol% MnO2. The additives were added in proportions to the calcined powder of the main component of the main phase. Ethanol was then added to the raw powder mixed with the additives, and the mixture was wet-mixed in a ball mill for 15 hours or more to obtain a slurry. The mixed powder with the additives added, obtained by drying the slurry, was calcined at 930°C for 4 hours in an air atmosphere to produce the calcined powder of the main phase.

[0064] Separately, the composition of the subphase is Ba2KNb5O 15 BaCO3 powder, K2CO3 powder, and Nb2O5 powder were weighed as raw material powders for the subphase so that the composition was as follows: Ethanol was added to these raw material powders for the subphase, and they were wet mixed in a ball mill for 15 hours or more to obtain a slurry. The mixed powder obtained by drying the slurry was calcined at 1150°C for 10 hours in an air atmosphere to produce calcined powder of the subphase.

[0065] The calcined powder of the main phase and the calcined powder of the subphase were weighed out so that the ratio of the subphase contained in the lead-free piezoelectric ceramic composition was 2 vol%. Next, ethanol and a binder were added to the weighed calcined powder of the main phase and the calcined powder of the subphase, and the mixture was wet-mixed in a ball mill for 15 hours or more to obtain a slurry. Then, the slurry was dried and the granulated powder was granulated. Then, the granulated powder was uniaxially pressed at a pressure of 20 MPa to form a doughnut shape. Then, a CIP process (cold isostatic pressing process) was performed at a pressure of 150 MPa to obtain a molded body. The obtained molded body (CIP pressed body) was sintered at 1140°C for 4 hours in an air atmosphere to obtain a piezoelectric body of Example 1.

[0066] Next, the obtained piezoelectric body was cut and the top and bottom surfaces were processed according to the dimensional accuracy required for the piezoelectric element. In order to stabilize the characteristics of the obtained piezoelectric body, an annealing treatment was performed under the condition of 100°C in air for 2 hours. After that, electrodes were attached by sputtering, and a polarization treatment was performed to produce the piezoelectric element of Example 1.

[0067] Example 2 The piezoelectric element of Example 2 was produced under the same conditions as those of the piezoelectric element of Example 1, except that the holding time during firing was 10 hours.

[0068] Example 3 The piezoelectric element of Example 3 was produced under the same conditions as those for the piezoelectric element of Example 1, except that the firing temperature was 1150° C. and the holding time was 10 hours.

[0069] Comparative Example 1 The piezoelectric element of Comparative Example 1 was produced under the same conditions as the piezoelectric element of Example 1, except that only the calcined powder of the main phase was used, and the lead-free piezoelectric ceramic composition did not contain a subphase. The firing temperature was 1130°C, and the holding time was 1 hour.

[0070] Comparative Example 2 The piezoelectric element of Comparative Example 2 was produced under the same conditions as those of the piezoelectric element of Example 1, except that the firing temperature was 1180° C. and the holding time was 10 hours.

[0071] [Test method for polarization] A voltage of 5 kV / mm was applied to the electrodes of the piezoelectric elements of Examples 1 and 2 and Comparative Example 1 to determine whether polarization was possible. If a current of 1 mA or more flowed when a voltage of 5 kV / mm was applied, it was determined that polarization was not possible.

[0072] [Method of measuring diffraction peaks] The piezoelectric elements of Example 1 and Example 2 prepared were pulverized using a pestle and mortar. The pulverized fine powder was filled into the tip of a capillary (φ=0.3 mm, Lindemann glass), and measurements were performed by the De Beischler method using monochromatic X-rays with a wavelength of 0.7 Å in the range of 2θ=0° to 70° in 0.01° steps. A 0.3 mm×0.5 mm beam was applied to the powder filled into the tip of the capillary to obtain diffraction peaks in the average structure of the entire piezoelectric element. The X-ray exposure time was 12 minutes.

[0073] X-ray diffraction measurement is a technique in which X-rays are incident on a sample from the horizontal direction at an angle of θ (at an angle of θ with respect to the crystal plane), and among the X-rays that are reflected from the sample, X-rays that are at an angle of 2θ with respect to the incident X-rays are detected to examine the change in intensity with respect to θ. In X-ray diffraction, the diffraction intensity increases when the Bragg condition (2dsinθ=nλ (λ: X-ray wavelength, d: atomic plane spacing of the crystal, n: integer)) is satisfied, and the crystal plane spacing (lattice constant) at that time corresponds to the above 2θ. Therefore, the crystal structure and orientation of the sample on which the X-rays are incident can be understood based on the value of 2θ at which the diffraction intensity increases.

[0074] [Calculation method for 020 / 002 peak ratio] Based on the obtained diffraction peaks, the ratio of maximum intensities of the peaks corresponding to the tetragonal peaks 020 and 002 in an alkali niobate perovskite oxide was calculated as 020 / 002.

[0075] [How to confirm the peaks of tungsten bronze compounds] Based on the obtained diffraction peaks, it was confirmed whether there was a peak at 13.2°±0.1° that was different from the main phase potassium niobate (alkali niobate perovskite-type oxide). In order to confirm that this peak was a tungsten bronze peak, it was also confirmed whether there were peaks at 11.5°±0.1° and 12.4°±0.1° that were different from the main phase.

[0076] [Piezoelectric constant d 33 Measurement method] The piezoelectric constant d of the sample composition 33 The piezoelectric constant d was measured using a d33 meter (ZJ-4B (Institute of Acoustics, Chinese Academy of Sciences)). 33 A piezoelectric property was determined to be high when the piezoelectric constant was 120 pC / N or higher.

[0077] [How to make a vibrator for evaluating vibration characteristics] In addition to the above piezoelectric element, two ring-shaped piezoelectric bodies were prepared for each of Examples 1 to 3 and Comparative Example 2, and the top and bottom surfaces were polished. Then, Ag electrodes were baked and polarization treatment was performed at 3.5 kV / mm. Copper electrodes were inserted between these samples, and the samples were stacked so that the polarization directions were paired, and further, they were sandwiched between metal blocks and then fastened with stainless steel bolts to produce a vibrator. In addition, two ring-shaped piezoelectric bodies made of a general PZT material were prepared, and a vibrator was produced in the same manner.

[0078] [Method of measuring vibration characteristics] An AC voltage was applied to the vibrator, and the vibration velocity of the element in 33 directions was measured with a laser Doppler vibrometer. A frequency characteristic analyzer (FRA5096 (NF)), an amplifier (HAS-4052 (NF)), and a laser Doppler vibrometer (NLV-2500 (Polytec)) were used for the measurement. The AC voltage output from the frequency characteristic analyzer and amplified by the amplifier was applied to the vibrator, and the vibration velocity at that time was measured with the laser Doppler vibrometer. The frequency of the applied voltage was set to be near the resonant frequency of the vibrator (about 67 kHz in the above example). Products that showed a value of 1.6 m / s or more when 13.5 Vrms / mm was applied were judged to be good products.

[0079] [result] 11 is a table showing various test results of the examples and comparative examples. In the piezoelectric element of Comparative Example 1, a current of 1 mA or more flowed when a voltage of 5 kV / mm was applied, so it was determined that polarization was not possible. In Examples 1 to 3 and Comparative Example 2, the current was less than 1 mA, so it was determined that polarization was possible.

[0080] 12 is a graph showing the diffraction peaks in a part of the angle range of the powder X-ray diffraction of Examples 1 to 3 and Comparative Example 2. The tetragonal peak 020 / 002 ratio of the main phase calculated based on these diffraction peaks was 1.53 for Example 1, 1.63 for Example 2, and 1.64 for Example 3. Also, it was 1.51 for Comparative Example 2. Taking this result into consideration with other test results, it is estimated that the boundary as to whether the piezoelectric properties of the lead-free piezoelectric ceramic composition forming the piezoelectric body are high or not is when the tetragonal peak 020 / 002 ratio of the main phase is around 1.52.

[0081] It was also confirmed that the diffraction peaks of the powder X-ray diffraction of Examples 1 to 3 and Comparative Example 2 showed a peak at 13.2°±0.1° that was different from the main phase. This confirmed that the lead-free piezoelectric ceramic compositions forming the piezoelectric bodies of Examples 1 to 3 and Comparative Example 2 contained a tungsten bronze type compound. It was also confirmed that the diffraction peaks of the powder X-ray diffraction of Examples 1 to 3 and Comparative Example 2 showed peaks at 11.5°±0.1° and 12.4°±0.1° that were different from the main phase.

[0082] The piezoelectric elements of Examples 1 to 3 have a piezoelectric constant d 33 In all cases, the piezoelectric constant d 33 was less than 120 pC / N.

[0083] FIG. 13 is a graph showing the vibration characteristics of vibrators made of Examples 1 to 3, Comparative Example 2, and general PZT. All of the vibrators for evaluating vibration characteristics made using the piezoelectric bodies of Examples 1 to 3 showed values ​​of 1.6 m / s or more when 13.5 Vrms / mm was applied, which was a higher value than that of a vibrator made of general PZT. Therefore, it was confirmed that the piezoelectric ceramic compositions of Examples 1 to 3 have good vibration characteristics and can suppress the deterioration of piezoelectric characteristics, especially vibration characteristics, under high voltage. On the other hand, the vibrator for evaluating vibration characteristics made using the piezoelectric body of Comparative Example 2 showed a value of about 0.5 m / s when 13.5 Vrms / mm was applied, which was a lower value than that of a vibrator made of general PZT.

[0084] The present invention is not limited to the above-described embodiment, and it goes without saying that various modifications and equivalents are included within the spirit and scope of the present invention. In addition, the structure, shape, number, position, size, etc. of the components shown in each drawing are for convenience of explanation and may be changed as appropriate. [Explanation of symbols]

[0085] 10: Piezoelectric element 20: Piezoelectric material 31,32: Electrode 40: Ultrasonic scalpel 41: Ultrasonic transducer 43: Working member 50: Ultrasonic scaler 53: Dental tip 60: Ultrasonic cleaner 63: Cleaning container 65: Items to be washed 70: Ultrasonic processing machine 71: Base material 75: Grindstone Department 77: Spindle 80: Piezoelectric transducer 90: Ultrasonic motor 93: Rota 95: Output shaft 100: Piezoelectric gyro sensor 110: Piezoelectric filter 120: Knock sensor

Claims

1. A main phase made of an alkali niobate perovskite oxide; and a subphase consisting of a tungsten bronze type compound, A lead-free piezoelectric ceramic composition, wherein the tetragonal peak 002 / 020 ratio of the main phase is 1.52 or more.

2. 2. The lead-free piezoelectric ceramic composition according to claim 1, wherein the tungsten bronze type compound exhibits a peak at 13.2°±0.1°.

3. 3. The lead-free piezoelectric ceramic composition according to claim 1, wherein the tungsten bronze type compound contains Nb and at least one of Ba, Ca, Sr, Na and K.

4. 3. The lead-free piezoelectric ceramic composition according to claim 1, wherein the alkali niobate perovskite oxide contains Mn.

5. The alkali niobate perovskite oxide has a composition formula (A1 a M1 b ) c (Nb d1 , Mn d2 , M2 d3 ) O 3+e 3. The lead-free piezoelectric ceramic composition according to claim 1, wherein the element A1 is at least one of alkali metals, the element M1 is at least one of Ba, Ca and Sr, the element M2 is at least one of Ti and Zr, 0<a<1, 0<b<1, a+b=1, c satisfies 0.80<c<1.10, 0<d1<1, 0<d2<1, 0<d3<1, d1+d2+d3=1, and e is a value indicating oxygen deficiency or excess), and b / (d2+d3)>1.0 is satisfied.

6. A piezoelectric element comprising a piezoelectric body made of the lead-free piezoelectric ceramic composition according to claim 1 or 2, and electrodes in contact with the piezoelectric body.

7. An apparatus comprising the piezoelectric element of claim 6.

8. The device according to claim 7 , which is selected from the group consisting of an ultrasonic scalpel, an ultrasonic scaler, an ultrasonic cleaner, an ultrasonic processing machine, a piezoelectric transducer, an ultrasonic motor, a piezoelectric gyro sensor, a piezoelectric filter, and a knock sensor.

Citation Information

Patent Citations

  • Lead-free piezoelectric porcelain composition and piezoelectric element

    WO2022215666A1

  • Lead-free piezoelectric magnetic composition and piezoelectric element

    WO2023026614A1